The New England Journal of Medicine Nº 26 (owned published, 2001)
Measurement of C-Reactive Protein for the Targeting of Statin Therapy in the Primary Prevention of Acute Coronary EventsLong-Term Effects of Indomethacin Prophylaxis in Extremely-Low-Birth-Weight InfantsTransfusion-Transmitted Malaria in the United States from 1963 through 1999Brief Report: Nephropathy and Establishment of a Renal Reservoir of HIV Type 1 during Primary InfectionTension PneumoperitoneumMedical Progress: Advances in Mechanical VentilationDrug Therapy: Side Effects of Adjuvant Treatment of Breast CancerCase 20-2001 ù A 64-Year-Old Man with Fever and Gram-Negative BacteremiaStatins and the Acute-Phase ResponseEcology in EvolutionThe Ecology of Medical Care RevisitedNoninvasive Ventilation in Immunosuppressed PatientsGene-Expression Profiles in Hereditary Breast CancerLiver BiopsyDiagnosis of Recurrent Astrocytoma with Fludeoxyglucose F18 PET ScanningSevered Trust: Why American Medicine Hasn`t Been FixedTalking about Health and Wellness with Patients: Integrating Health Promotion and Disease Prevention into Your PracticeCrime and Elder Abuse: An Integrated Perspective